The Effect Of Addition Of Fruit Sari (Dimorcarpus Longan) To Skim Milk In Yoghurt Drink - Reza Noprianto; Ririn Anggreany; Rita Agustina; Saskia Anggun.K; Yuyun Apitasari; Nurlia latipah (ISEJ : Indonesian Science Education Journal, 2020)
An effort in dairy products is currently growing, this is also because milk is a product that is easily damaged. Yogurt is one type of fermented milk that has been widely known by the public. Milk fermentation technology is developing quite rapidly by utilizing many pure and single cultures as well as the use of other lactic acid bacteria that can provide better product quality. This study aims to determine: 1) the effect of the amount of longan extract on skim milk; 2) the effect of the amount of skim milk on the nature of yakult. The method used is an experimental method that uses two factors, namely the addition of longan fruit extract and skim milk. The results showed that there was an effect of the addition of longan juice in the form of taste, color, and thickness. Based on the results of the study it can be concluded that the addition of longan fruit extract to yogurt does not affect the acidity of yougurt, because the levels of longan fruit extract are small, so that the acidity level on yougurt is still high